Environmentally Benign Phytic Acid-Based Nanocoating for Multifunctional Flame-Retardant/Antibacterial Cotton - Eva Magovac; Bojana Vončina; Ana Budimir; Igor Jordanov; Jaime C. Grunlan; Sandra Bischof (Fibers, 2021)
Environmentally benign layer-by-layer (LbL) deposition was used to obtain flame-retardant and antimicrobial cotton. Cotton was coated with 8, 10, and 12 phytic acid (PA) and chitosan (CH)-urea bilayers (BL) and then immersed into copper (II) sulfate (CuSO4) solution. Our findings were that 12 BL of PA/CH-urea + Cu2+ were able to stop flame on cotton during vertical flammability testing (VFT) with a limiting oxygen index (LOI) value of 26%. Microscale combustion calorimeter (MCC) data showed a reduction of peak heat release rates (pHRR) of more than 61%, while the reduction of total heat release (THR) was more than 54%, relative to untreated cotton. TG-IR analysis of 12 BL-treated cotton showed the release of water, methane, carbon dioxide, carbon monoxide, and aldehydes, while by adding Cu2+ ions, the treated cotton produces a lower amount of methane. Treated cotton also showed no levoglucosan. The intumescent behavior of the treatment was indicated by the bubbled structure of the post-burn char. Antibacterial testing showed a 100% reduction of Klebsiella pneumoniae and Staphylococcus aureus. In this study, cotton was successfully functionalized with a multifunctional ecologically benign flame-retardant and antibacterial nanocoating, by means of LbL deposition.